Analisis Keberhasilan Implementasi Manajemen Mutu ISO 21001:2018 di Pondok Pesantren Nurul Jadid Berbasis Model PDCA dan Teori Total Quality Management - Mujiburrohman; Hasan Baharun (Khatulistiwa Insight: Islamic Education and Learning, 2025)
This study aims to analyze the success of implementing ISO 21001:2018 quality management at Pondok Pesantren Nurul Jadid Paiton Probolinggo using the PDCA (Plan-Do-Check-Act) cycle approach and the integration of Total Quality Management (TQM) theory. The background of this research is based on the urgency of improving the quality of pesantren-based educational institutions through international standards that are relevant to the context of Islamic education. This study employs a qualitative approach with a case study method. Data collection techniques include in-depth interviews, participatory observation, and documentation, involving various stakeholders such as pesantren leaders, the education bureau, teachers, students (santri), parents, alumni, and internal auditors. The results show that the systematic application of the PDCA cycle has positively impacted the effectiveness of educational management and services. The stages of planning, implementation, evaluation, and follow-up have been well-executed, reflecting the involvement of all institutional components. Moreover, TQM values such as customer focus, employee involvement, process approach, integrated systems, and continuous improvement have been internalized in the pesantren’s work culture. The integration of ISO 21001:2018 has also had a positive impact on stakeholder satisfaction and performance, as reflected in increased participation, transparency, and accountability in institutional management. The study recommends strengthening human resource training, digitizing the quality system, and conducting participatory evaluations as follow-up steps for sustainable quality improvement. These findings demonstrate that the implementation of international quality standards can be effectively and harmoniously integrated within pesantren culture, serving as a contextual and sustainable model for improving the quality of Islamic education.